Switchable subwavelength plasmonic structures with phase-change materials for reflection-type active metasurfaces in the visible region. (2nd November 2017) - Hwang, Chi-Young; Lee, Seung-Yeol; Kim, Yong-Hae; Kim, Tae-Youb; Kim, Gi Heon; Yang, Jong-Heon; Pi, Jae-Eun; Choi, Ji Hun; Choi, Kyunghee; Kim, Hee-Ok; Hwang, Chi-Sun
Abstract: In this work, a switchable plasmonic structure is proposed for reflection-type spatial light modulation in the visible range with subwavelength resolution. This structure is based on a metallic grating in which each resonant cavity couples the incident light into a gap surface plasmon mode and then reflects the light modulated in the cavity. By incorporating an ultrathin layer of the phase-change material Ge2 Sb2 Te5 at the entrance of the cavity, the optical modulation characteristic of the structure can be switched between two modes. Numerical investigations are conducted to verify the proposed structure, with the focused analysis of two common types of binary modulations: amplitude-only and phase-only modulations.